The Consortium of Metabolomics Studies (COMETS): Metabolomics in 47 Prospective Cohort Studies. Issue 6 (19th February 2019) - Yu, Bing; Zanetti, Krista A; Temprosa, Marinella; Albanes, Demetrius; Appel, Nathan; Barrera, Clara Barrios; Ben-Shlomo, Yoav; Boerwinkle, Eric; Casas, Juan P; Clish, Clary; Dale, Caroline; Dehghan, Abbas; et al.
Abstract: The Consortium of Metabolomics Studies (COMETS) was established in 2014 to facilitate large-scale collaborative research on the human metabolome and its relationship with disease etiology, diagnosis, and prognosis. COMETS comprises 47 cohorts from Asia, Europe, North America, and South America that together include more than 136, 000 participants with blood metabolomics data on samples collected from 1985 to 2017. Metabolomics data were provided by 17 different platforms, with the most frequently used labs being Metabolon, Inc. (14 cohorts), the Broad Institute (15 cohorts), and Nightingale Health (11 cohorts). Participants have been followed for a median of 23 years for health outcomes including death, cancer, cardiovascular disease, diabetes, and others; many of the studies are ongoing. Available exposure-related data include common clinical measurements and behavioral factors, as well as genome-wide genotype data. Two feasibility studies were conducted to evaluate the comparability of metabolomics platforms used by COMETS cohorts. The first study showed that the overlap between any 2 different laboratories ranged from 6 to 121 metabolites at 5 leading laboratories. The second study showed that the median Spearman correlation comparing 111 overlapping metabolites captured by Metabolon and the Broad Institute was 0.79 (interquartile range, 0.56–0.89).